Structural and optical properties of (112̅2) InGaN quantum wells compared to (0001) and (112̅0). (12th July 2016) - Pristovsek, Markus; Han, Yisong; Zhu, Tongtong; Oehler, Fabrice; Tang, Fengzai; Oliver, Rachel A; Humphreys, Colin J; Tytko, Darius; Choi, Pyuck-Pa; Raabe, Dierk; Brunner, Frank; Weyers, Markus
Abstract: We benchmarked growth, microstructure and photo luminescence (PL) of (112̅2) InGaN quantum wells (QWs) against (0001) and (112̅0). In incorporation, growth rate and the critical thickness of (112̅2) QWs are slightly lower than (0001) QWs, while the In incorporation on (112̅0) is reduced by a factor of three. A small step-bunching causes slight fluctuations of the emission wavelength. Transmission electron microscopy as well as atom probe tomography (APT) found very flat interfaces with little In segregation even for 20% In content. APT frequency distribution analysis revealed some deviation from a random InGaN alloy, but not as severe as for (112̅0). The slight deviation of (112̅2) QWs from an ideal random alloy did not broaden the 300 K PL, the line widths were similar for (112̅2) and (0001) while (112̅0) QWs were broader. Despite the high structural quality and narrow PL, the integrated PL signal at 300 K was about 4 × lower on (112̅2) and more than 10 × lower on (112̅0).